Management of public sector in India (Bombay : Published on behalf of Commerce [by] Vora, 1971)
The public sector in India dominate the economic scene both in depth and width of coverage with an investment of over Rs 3500 crores provide the basic infrastructure needed for building a modern industrial economy
Includes bibliographical references.
oo 12/11/2018
Loans
Keywords: Government business enterprises